Clinical cardiac MRI with interactive CD-ROM - Bogaert, Jan. (Medical radiology, diagnostic imaging, 2005)
MRI has become the preferred noninvasive imaging modality for the heart and great vessels. The substantial technological progress achieved in recent years has provided the user with state of the art MRI systems, but their optimal use can be limited by restricted awareness of the potential patient benefit and the necessity for teaching. This extensively illustrated volume, has been specifically compiled to meet these needs. Essential theoretical background information is provided, and imaging acquisition and potential pitfalls are considered in detail. Most importantly, structured guidelines are provided on the interpretation of clinical data in the wide range of cardiac pathology that can be encountered. Throughout, the emphasis is on the implementation of cardiac MRI in clinical practice. Cardiac MRI physics -- Contrast agents for cardiac MRI -- Practical setup -- Cardiac anatomy -- Cardiovascular MR imaging planes and segmentation -- Cardiac function -- Myocardial perfusion -- Ischemic heart disease -- Nonischemic myocardial disease -- Heart failure, pulmonary hypertension, and heart transplantation -- Pericardial disease -- Cardiac masses -- Valvular heart disease -- Coronary artery disease -- Congenital heart disease -- Imaging of great vessels -- MR-guided cardiac catheterization -- General conclusions.